The Lost and Found Bookshop - Wiggs, Susan (William Morrow, an imprint of Harper Collins Publishers, 2020)
Natalie Harper feels she must sell the bookshop she's inherited to pay for her grandfather's care, but he refuses to acquiesce, and renovation of the store and its studio apartment push her life in a whole new direction. Besides, she loves the store and its books provide welcome solace for her overwhelming grief. After she moves into the small studio apartment above the shop, Natalie carries out her grandfather's request and hires contractor Peach Gallagher to do the necessary and ongoing repairs. His young daughter, Dorothy, also becomes a regular at the store, and she and Natalie begin reading together while Peach works."